Al-Qirā’āt as-Sab‘ In The Tafsīr Marāh Labīd By Syaikh Nawāwi al-Bantāni (Guidance On The Reading Sūrat an-Nisā’): القراءات السبع في تفسير مرَاح لَبِيد لشيخ نووي البنتاني (توجيه القراءات في سورة النساء) - Natasya, Hana; Anisa, Nur; Yousuf, Ramy (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2025)
This research aims to analyze qirā’āh sab‘ah in Surah an-Nisā’ [4] as explained in the tafsir Marāḥ Labīd by Sheikh Nawawi Al-Bantani, focusing on the variations of qirā’āt that fall under the rule of farsy al-ḥurūf. This study is significant in uncovering the use of the seven Quranic readings (qira'at sab'ah) in Nusantara exegesis and the extent of their influence on the interpretations of scholars. Given that Sheikh Nawawi is one of the prominent Nusantara scholars whose tafsir is widely referenced by exegetes. This research adopts a library-based approach (library research) with a descriptive-analytical method. The analytical steps include presenting the words containing farsy al-ḥurūf in Surah an-Nisā’ [4] and examining their meanings and implications using the taujīh al-qirā’āt approach. The findings indicate that Surah an-Nisā’ contains 49 words from 43 verses classified under the rule of farsy al-ḥurūf. In Marāḥ Labīd, 23 words from 21 verses employing qirā’āh sab’ah are identified. The novelty of this research lies in three aspects, the study of qirā’āh sab’ah in traditional tafsir, particularly in Marāḥ Labīd. the application of the taujīh al-qirā’āt approach, providing a new perspective on how variations in Qur'anic readings can be explained and understood in linguistic, theological, and exegetical contexts. The contribution to the study of Nusantara tafsir, highlighting the works of local scholars and broadening the discourse of Qur'anic Studies. This research significantly enhances the understanding of qirā’āh and tafsir, particularly in the context of traditional Islamic scholarship in the Nusantara region.